Council Highlights: Minutes of the 541st, 542nd and 543rd Meetings of the Council (1968)
This summary is published so that CMA membership may be advised in brief of the actions of the Association's Council. It covers only major actions and is not intended as a detailed report. Full minutes of these meetings are available upon any member's request to the CMA office.